Cervical cancer screening practices in HIV positive females – a missing link in health care delivery in Pakistan - Idrak, Sobia; Zaki, Saima; Rasheed, Farhan; Javed, Maham; Khalid, Huma; Niaz, Sumaira; Romeeza Tahir; Naseem, Nadia (Journal of the Pakistan Medical Association, 2024)
Objective: To probe cervical cancer screening practices in local women positive for human immunodeficiency virus, and to determine the cervical cytological changes in them. Method: The serial cross-sectional study was conducted at the Jinnah Hospital and Services Hospital, Lahore, Pakistan, from April 2019 to October 2020, and comprised female patients aged 18-45 years who were positive for human immunodeficiency virus or acquired immunodeficiency syndrome and were registered with the relevant programme being run by the provincial government in Punjab. Blood samples of all the patients were collected for the determination of human immunodeficiency virus viral load and cluster of differentiation 4+ count. Cervical smears were taken for cytopathological analysis, while the swabs were analysed for culture sensitivity. The same individuals were subjected to the same testing one year later, and the status of the disease and clinical stability or disease progression was explored. Data was analysed using SPSS 25. Results: There were 150 women with mean age 32.08±7.13 years (range: 21-45 years). Age at marriage/sexual activity was 17.33±4.73 years in 15(10%) subjects. Cytological examination showed atypical squamous cells of undetermined significance in 6(4%) of the cases whereas 3(2%) cases showed atypical squamous cells, which cannot rule out high grade squamous intraepithelial lesion on cytology, while the rest were classified as negative for intraepithelial lesion or malignancy. Cervical microbial changes revealed methicillin-resistant staphylococcus aureus infection in 9(6%) cases, extended-spectrum beta-lactamase in 15(10%) cases, whereas fungal infection and trichomonas vaginalis infection were found in 30(20%) smears. There was a significant association between cluster of differentiation 4+ cell count and stability of high-risk patients (p<0.001). After one year, 84(56%) patients remained clinically stable, while 51(34%) developed some chronic illness. There was a significant association between cluster of differentiation 4+ cell count <200/mm 3 and the risk of developing a chronic illness (p<0.001). Conclusion: There was a dire need to educate healthcare workers to offer regular cervical screening to patients with high-risk sexually-transmitted infections to prevent them from the morbidity and mortality related to cervical cancer. Key Words: HIV/AIDS, Cervical cancer, Screening, Bethesda system.